Availability, Costs and Stock-Outs of Essential NCD Drugs in Three Rural Rwandan Districts - Jean Paul Mukundiyukuri; Jean Jacques Irakiza; Naome Nyirahabimana; Loise Ng’ang’a; Paul H. Park; Gedeon Ngoga; Ziad El-Khatib; Louis Nditunze; Etienne Dusengeyezu; Christian Rusangwa; Tharcisse Mpunga; Joel Mubiligi; et al. (Annals of Global Health, 2020)
Background: To reduce the non-communicable diseases (NCDs) burden, the World Health Organization has set a target to reach 80% availability of the affordable essential medicines required to treat NCDs by 2025. Objectives: This study described the availability, costs, and stock-outs of essential NCD drugs in three rural Rwandan districts. Methods: We retrospectively assessed 54 NCD drugs listed for district hospitals or health centers in the Rwanda national essential medicines list. Data were collected from three district hospitals and 17 health centers that host NCD clinics. We extracted data on drug availability, quantity dispensed, costs, stock-outs, and the replenishing supplier for these drugs between January 1 and December 31, 2017. Results: Overall, 71% of essential medicines for health centers and 78% of essential medicines for district hospitals were available at facilities. Only 15% of health centers experienced a stock-out of beclomethasone, while 77% experienced at least one stock-out of amlodipine and metformin. The median length of stock-out ranged from nine to 72 days, and 78% of the stock-outs across all health centers were replenished by a Non-Governmental Organization (NGO) partner. Except for enoxaparin and metformin, all district hospitals experienced at least one stock-out of each drug. The median length of stock-out ranged from 3.5 to 228 days, and 82% of the stock-outs across all district hospitals were replenished by the Rwandan Ministry of Health (RMOH). The least expensive drug was digoxin ($0.02, Interquartile range (IQR): 0.01, 0.10), while the most expensive was beclomethasone ($9.35, IQR: 3.00, 13.20). Conclusions: This study shows the viability of drug-supported NCD care in rural settings of sub-Saharan Africa. Stock-outs are a challenge; our study emphasizes the importance of the MOH/NGO partnerships in this context. Medicine costs are also challenging, though, in these districts, drugs are more affordable through community-based health insurance, government, and NGO partner subsidies.